Strategi Manajemen Risiko Operasional dan Reputasi dalam Menghadapi Dinamika Pasar Global: Studi Kasus Nestlé - Jayanti Patricia; Desinta Nirmala Wulandari; Fransiska Kolo; Yessy Christien Novela Abigail Boru Raja Gukguk; Alvianus Kristian (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the operational and reputational risk management strategies implemented by Nestlé in navigating the increasingly complex dynamics of the global market. The analysis focuses on how the company integrates cross-functional risk governance, strengthens supply chain resilience, and reinforces public trust through sustainability initiatives and transparent communication. The research employs a literature-based method drawing from Nestlé’s official reports, academic publications, and relevant global management literature. The findings indicate that geographic diversification, digital transformation, and cost control measures effectively reduce operational volatility and sustain financial performance stability. Meanwhile, the enhancement of supplier ethics, improved quality standards, and strategic public communication play a crucial role in mitigating reputational risks. The integration of these two risk domains creates a synergistic framework that improves global-local adaptability, especially when the company encounters geopolitical disruptions, economic fluctuations, and shifting global consumer preferences. The study underscores that competitive advantage for multinational corporations is not solely determined by production capacity and internal efficiency, but also by the ability to manage public perception consistently across different markets. These findings are expected to contribute to the advancement of integrated risk management approaches within the global food industry.